The disagreement between protests and elections in Colombia (2010-2015) - Cruz Rodríguez, Edwin (2016)
Between 2010 and 2015, the most important protest cycle in the history of Colombia takes place, organized by leftist social organizations. At the same time, the Polo Democrático Alternativo, the main leftist party, experiences an electoral decline and the fragmentation of its internal tendencies. Consequently, the Colombian left fails to translate the discontent of social protest into electoral results. This article analyzes the disagreement between protests and elections, arguing that it is a result, on the one hand, of structural constraints characteristic of a political system in which electoral politics is not separated from violence and, on the other hand, the inability of the left to generate frameworks of collective action capable of challenging voters beyond the identities that exclude their different tendencies.